PENDEKATAN BIOETIK TENTANG EUTANASIA - Wakiran, Mutiara D. B. I.; Tomuka, Djemi Ch.; Kristanto, Erwin G. (Jurnal Biomedik : JBM, 2013)
Abstract: Generally, a patient desires a ‘normal’ death free from pain and fear which is called in medical terms: euthanasia. Nowadays, euthanasia is a dilemmatic issue among doctors. Medical ethics has become a broader consideration which has developed quite rapidly in the last three decades; therefore, ethical considerations have become major concerns in the medical profession. They are often found in conflict especially between a doctor and a patient, and these can not be solved by using the traditional rules of medical ethics. In such cases, the rules of law, depending on region or nation, can be enforced, so that the problem under discussion (euthanasia) can not be separated from the issues of the rights and obligations of the involved parties. The rapid development in medical science and biology creates more complex problems which can not be solved by long-standing medical ethics; therefore, bioethics has been developed in the expectation of providing more available and logical solutions. Keywords: euthanasia, death, conflict.   Abstrak: Kematian yang diidamkan oleh para penderita ialah kematian yang normal, jauh dari rasa sakit dan mengerikan yang dalam istilah medis disebut eutanasia. Eutanasia merupakan suatu persoalan yang dilematik baik di kalangan dokter. Etika telah menjadi suatu bagian dari dunia kedokteran yang cukup pesat perkembanganya dalam tiga dekade terakhir dan pertimbangan etika menjadi perhatian utama dalam pelaksanaan profesi kedokteran. Dalam profesi ini seringkali dijumpai konflik antara dokter dan pasien yang tidak dapat dipecahkan oleh kaidah-kaidah etika. Dalam hal seperti ini maka kaidah-kaidah hukum dapat dapat diberlakukan, sehingga pembicaraan tidak dapat dilepaskan dari masalah hak dan kewajiban dari pihak-pihak yang yang terlibat dalam permasalahan tersebut. Perkembangan yang pesat dalam ilmu kedokteran dan biologi serta permasalahan yang mengiringinya semakin kompleks sehingga kajian tentang etika kedokteran yang membahas mengenai bidang medis dan profesi kedokteran saja tidak cukup; untuk itu dikembangkan bioetika (etika biomedis) yang diharapkan dapat menghasilkan solusi yang lebih dapat diterima dan logik. Kata kunci: euthanasia, etika, konflik.